DICAR/DICAR-JP exerts therapeutic effects in brain stroke via the miR-361-5p/PRMT1 pathway - Yu, Zhijun; Jiang, Aihua; Yang, Kai; Zhan, Lin; Xiang, Zifei; Chen, Li; Kuai, Zheng; Yuan, Qiong (Frontiers in Pharmacology, 2025)
BackgroundAngiogenesis is an important mechanism in stroke therapy. Circular RNA-DICAR is known to protect against diabetes-induced cardiomyocyte pyroptosis. In this study, we examined the effect of DICAR on angiogenesis as well as the therapeutic effect of DICAR-JP, which is its functional domain, against stroke. The mechanism involves the miR-361-5p/PRMT1 signaling pathway. Moreover, the middle cerebral artery occlusion/reperfusion (MCAO) method was used to establish a mouse stroke model in the DICAR-Tg mouse model.MethodsAAV9-DICAR-JP was constructed and injected into the cerebral ventricles. Furthermore, tube formation assays were used to evaluate the in vitro activity of DICAR-JP. The blood flow was tested by Laser Speckle Flowgraphy. The expressions of PRMT1 protein expression was evaluated by Western blotting (WB). The binding ability was evaluated by luciferase reporter.ResultsResults indicated that DICAR-Tg improved neuronal function. AAV9-DICAR-JP increased blood flow in the brain following stroke. DICAR-siRNA upregulated miR-361-5p expression, and overexpression of miR-361-5p significantly reduced PRMT1 expression.ConclusionDICAR/DICAR-JP has potential therapeutic benefits in stroke, which is mediated by the miR-361-5p/PRMT1 signaling pathway.